Implementation of Sharia-Based Human Resource Management at Bank Syariah Indonesia KCP Surabaya MERR 2 - Satunggale Kurniawan; Chusnul Chabibah Ilhama (Jurnal Ekonomi Islam, 2025)
This study examines the implementation of sharia-based human resource management (HRM) at Bank Syariah Indonesia (BSI) Sub-Branch Office Surabaya MERR 2. The rapid growth of Islamic banking in Indonesia requires institutions to manage human resources not only professionally but also in accordance with Islamic principles such as honesty, trustworthiness, justice, and responsibility. The objective of this research is to analyze how sharia values are integrated into HRM practices and to identify their impact on employee performance and service quality. This research employs a qualitative descriptive approach, with data collected through in-depth interviews, observations, and documentation. The findings indicate that sharia-based HRM has been systematically implemented across key functions, including workforce planning, recruitment and selection, training and development, performance appraisal, and compensation systems. Recruitment emphasizes both technical competence and moral integrity, while training programs combine professional skills with spiritual development. Performance evaluations are conducted objectively and transparently, reflecting the principle of fairness, and compensation is provided appropriately in accordance with sharia guidelines. The implementation of these values has positively influenced employee discipline, professionalism, and accountability, ultimately enhancing customer trust and satisfaction. This study contributes empirical evidence that sharia-based HRM can be effectively applied at the sub-branch level despite operational challenges and resource limitations, and it offers practical insights for strengthening Islamic HRM practices in the banking sector.